CSIG-25. MTAP LOSS COMPROMISES DNA DAMAGE RESPONSE IN GBM CELLS. (11th November 2019) - Du, Changzheng; Hansen, Landon; Singh, Simranjit; Roso, Kristen; Greer, Paula; He, Yiping
Abstract: Homozygous deletion of methylthioadenosine phosphorylase (MTAP) is one of the most frequent genetic alterations in glioblastomas (GBMs), occurring in about half of all patients. Here, we demonstrated that MTAP loss compromises the proteostasis of genomic stability guardian, H2AX, via disrupting a signaling cascade of PRMT5-RNF168-SMURF2. We showed that PRMT5 sustains the expression of RNF168, an E3 ubiquitin ligase essential for cellular response to DNA damage. Suppression of PRMT5 function, as occurring in MTAP-null GBM cells, attenuates the expression of RNF168, which consequently leads to degradation of H2AX protein by a HECT-type E3 ubiquitin ligase, SMURF2. We revealed that RNF168 and SMURF2, serving as a stabilizer and destabilizer of H2AX respectively, functionally oppose each other via their dynamic interactions with H2AX. In supporting the important role of this PRMT5-RNF168-SMURF2 signaling cascade in controlling H2AX homeostasis, MTAP-null GBM cells display a compromised DNA damage response, highlighted by higher levels of DNA damage spontaneously or in response to genotoxic agents. Collectively, these results identify a novel signaling cascade that is essential to the DNA damage response, reveal the profound impact of MTAP loss on GBM cells, and suggest novel therapeutic opportunities.